Vegetation and environmental dynamics in the southern Black Sea region since 18 kyr BP derived from the marine core 22-GC3. - Shumilovskikh, Lyudmila S; Tarasov, Pavel E; Arz, Helge W; Fleitmann, Dominik; Marret, Fabienne; Nowaczyk, Norbert R; Plessen, Birgit; Schlütz, Frank; Behling, Hermann (PANGAEA, 2012)
Sediments from the Black Sea, a region historically dominated by forests and steppe landscapes, are a valuable source of detailed information on the changes in regional terrestrial and aquatic environments at decadal to millennial scales. Here we present multi-proxy environmental records (pollen, dinoflagellate cysts, Ca, Ti and oxygen isotope data) from the uppermost 305 cm of the core 22-GC3 (42°13.53' N, 36°29.55' E) collected from a water depth of 838 m in the southern part of the Black Sea in 2007. The records span the last ~ 18 kyr (all ages are given in cal kyr BP). The pollen data reveal the dominance of the Artemisia-steppe in the region, suggesting rather dry/cold environments ~ 18-14.5 kyr BP. Warming/humidity increase during melt-water pulses (~ 16.1-14.5 kyr BP), indicated by d18O records from the 22-GC3 core sediment and from the Sofular Cave stalagmite, is expressed in more negative d13C values from the Sofular Cave, usually interpreted as the spreading of C3 plants. The records representing the interstadial complex (~ 14.5-12.9 kyr BP) show an increase in temperature and moisture, indicated by forest development, increased primary productivity and reduced surface run-off, whereas the switch from primary terrigenous to primary authigenic Ca origin occurs ~ 500 yr later. The Younger Dryas cooling is clearly demonstrated by more negative d13C values from the Sofular Cave and a reduction of pines. The early Holocene (11.7-8.5 kyr BP) interval reveals relatively dry conditions compared to the mostly moist and warm middle Holocene (8.5-5 kyr BP), which is characterized by the establishment of the species-rich warm mixed and temperate deciduous forests in the low elevation belt, temperate deciduous beech-hornbeam forests in the middle and cool conifer forest in upper mountain belt. The border between the early and middle Holocene in the vegetation records coincides with the opening of the Mediterranean corridor at ~ 8.3 kyr BP, as indicated by a marked change in the dinocyst assemblages and in the sediment lithology. Changes in the pollen assemblages indicate a reduction in forest cover after ~ 5 kyr BP, which was likely caused by increased anthropogenic pressure on the regional vegetation.
Pollen profile and age determination for sediment core M72/5_619-1 (22-GC3)
Keywords: 22-GC3; 24-GC3; Black Sea; GC; Gravity corer; M72/5; M72/5_619-1; M72/5_625-1; Meteor (1986)